Computational Biomechanics for Medicine From Algorithms to Models and Applications - Wittek, Adam; Joldes, Grand; Nielsen, Poul M.F; Doyle, Barry J.; Miller, Karol (Springer International Publishing : Imprint: Springer, 2017)
This volume comprises the latest developments in both fundamental science and patient-specific applications, discussing topics such as: cellular mechanics; injury biomechanics; biomechanics of heart and vascular system; medical image analysis; and both patient-specific fluid dynamics and solid mechanics simulations. With contributions from researchers world-wide, the Computational Biomechanics for Medicine series of titles provides an opportunity for specialists in computational biomechanics to present their latest methodologies and advancements.